2021
DOI: 10.1177/10901981211014101
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Disorders During the COVID-19 Outbreak in Spain: The Role of Sociodemographic Risk Factors and Cognitive Emotion Regulation Strategies

Abstract: Background Cognitive emotion regulation strategies (CERS) play a transdiagnostic role in emotional disorders, but the role of these strategies in coping with emotions during the coronavirus disease 2019 (COVID-19) pandemic remains poorly understood. Aims To assess the presence of emotional disorders in Spain and the association to sociodemographic characteristics and CERS during the COVID-19 outbreak. Method Cross-sectional survey administered through an online platform. Sociodemographic variables and CERS (CE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
1
17
0
2
Order By: Relevance
“…In our search, a few cutting-edge papers were found, in which associations between conventional categories were investigated with sound methodology e.g. [ 29 , 31 , 32 ]. The benefit of these cutting-edge papers is in showing the long-term impact of the COVID-19 pandemic on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In our search, a few cutting-edge papers were found, in which associations between conventional categories were investigated with sound methodology e.g. [ 29 , 31 , 32 ]. The benefit of these cutting-edge papers is in showing the long-term impact of the COVID-19 pandemic on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…El propósito principal de este estudio fue explorar la relación entre el afrontamiento resiliente y el FoMO, e investigar el posible efecto moderador de la regulación emocional sobre dicha relación en periodo de pandemia por Covid-19. Como se ha señalado anteriormente, existe evidencia sobre el papel protector que, ante eventos vitales estresantes como lo está siendo el actual periodo de pandemia, ejercen de manera individual el afrontamiento resiliente (Keener et al, 2021;Li et al, 2021;Salah et al, 2021) y la regulación emocional (Gutirrez-Cobo et al, 2021;Limonero et al, 2006;Liniana & Long, 2002;Muñoz-Navarro et al, 2021;Sun et al, 2021). Sin embargo, el presente estudio se centra en conocer si ambos recursos personales ejercen un papel protector frente a una de las consecuencias nocivas asociadas a este periodo, el FoMO.…”
Section: Discussionunclassified
“…En este sentido, el estudio llevado a cabo por Sun et al (2021) durante el periodo de pandemia, evidenciaron que contar con bajos niveles de regulación emocional se relacionaba con mayores índices de depresión y emociones negativas. A su vez, una de las estrategias de regulación emocional conocida como reevaluación cognitiva, ha sido relacionada positivamente con el nivel de felicidad (Gutiérrez-Cobo et al, 2021), así como se ha relacionado negativamente con el grado de ansiedad (Muñoz-Navarro et al, 2021) a lo largo de este periodo. Por tanto, podría considerarse la regulación emocional como un factor protector frente a consecuencias indeseables asociadas a la pandemia.…”
Section: Introductionunclassified
“…Within all the named symptoms of the unemployed syndrome, losing the meaning of life and individual functioning is the most struggling for many individuals, which is the culprit that can give people the biggest blow (Thill et al, 2020;Levy and Cohen-Louck, 2021;Rosen and Stenbeck, 2021). As employment and personal/household income are the most direct factors related to individuals' mental health conditions in their daily lives, we summarized existed studies that compared unemployed individuals and employed individuals regarding their mental health problems in Table 2 (Banna et al, 2020;Liu et al, 2020;Patabendige et al, 2020;Ueda et al, 2020;Verma and Mishra, 2020;Hassannia et al, 2021;Munoz-Navarro et al, 2021) and the association between income and mental health problems in Table 3 (Banna et al, 2020;Naser et al, 2020;Que et al, 2020;Shi et al, 2020;Verma and Mishra, 2020;Munoz-Navarro et al, 2021;Zheng et al, 2021a). By comparing symptoms of anxiety and stress between the employed and unemployed, Banna et al (2020) reported that unemployed individuals were three times more likely than the employed to have anxiety symptoms and two times more likely to have stress (Banna et al, 2020).…”
Section: Unemployment Under Covid-19 and Associated Mental Health Pro...mentioning
confidence: 99%